The influence of physical Activity on handgrip strength of elderly - Lovorka Bilajac; Denis Juraga; Hela Zuljevic; Mihaela Marinovic Glavic; Vanja Vasiljev; Tomislav Rukavina (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2019)
The global population aged 60 years and over will reach nearly 2.1 billion by 2050. During the aging process, the strength of the musculoskeletal system decreases and it is essential to be moderately physically action to prevent negative changes in muscle cells. Because the handgrip strength test is a robust predictor of the overall state of strength and physical frailty, it was used in this study to demonstrate physical functionality and muscle weakness related to physical activity. Examinees who participated in the study were elderly people aged 60 years and older who regularly performed exercises twice a week under the guidance of physiotherapy students.